Tension Leg Rectangular Fish Cage Motion Analysis in Regular and Random Waves - Raditya Danu Riyanto; Yuni Ari Wibowo; Mochammad Ramzi (Department of Ocean Engineering, 2022)
This paper uses an analytical method to examine the motion of a Tension Leg Fish Cage (TLFC) in regular and random waves. TLFC is a conceptual design of a fish cage based on the Tension Leg Platform (TLP) working principle that is usually used in deep water offshore oil and gas exploration. The idea of providing a safe environment to combine ecotourism and fish farming in a single platform led us to perform an analytical calculation to assess the possibility of using the TLP concept in fish farming. A preliminary conceptual design of TLFC using an HDPE floater with steel cable tendon is presented. The analytical calculation of the response amplitude operator for surge and heave motion is presented using linear airy wave theory with head seas encountering angle. This paper also presents the calculation of TLFC surge and heave motion under random wave loads. The random wave spectra used in this paper are JONSWAP and ISSC spectra. The result shows that the surge and heave motion response of TLFC is relatively smalland, therefore, can be analyzed further with more detailed consideration. It is admitted that HDPE is a brittle material that cannot sustain any long period of constant tension. Hence the optimum tendon-floater connection for the structure is subject to further research.